2023
DOI: 10.1002/jhm.13101
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic clinical decision support for pneumonia in the ED: A randomized trial

Abstract: Background Electronic health record‐based clinical decision support (CDS) is a promising antibiotic stewardship strategy. Few studies have evaluated the effectiveness of antibiotic CDS in the pediatric emergency department (ED). Objective To compare the effectiveness of antibiotic CDS vs. usual care for promoting guideline‐concordant antibiotic prescribing for pneumonia in the pediatric ED. Design Pragmatic randomized clinical trial. Setting and Participants Encounters for children (6 months‐18 years) with pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Typically, PP analyses will report stronger findings than ITT analyses. For example, a recent RCT considered the effectiveness of clinical decision support, compared with usual care, for guideline‐concordant antibiotic prescribing 8 . There were 321 usual care and 214 intervention participants in the ITT analyses, with a small favorable result observed (odds ratio [OR]: 1.08; 95% confidence interval [CI]: 0.76, 1.53).…”
Section: Different Types Of Analysis Proceduresmentioning
confidence: 99%
“…Typically, PP analyses will report stronger findings than ITT analyses. For example, a recent RCT considered the effectiveness of clinical decision support, compared with usual care, for guideline‐concordant antibiotic prescribing 8 . There were 321 usual care and 214 intervention participants in the ITT analyses, with a small favorable result observed (odds ratio [OR]: 1.08; 95% confidence interval [CI]: 0.76, 1.53).…”
Section: Different Types Of Analysis Proceduresmentioning
confidence: 99%
“…The PIS at the VUMC is a natural language processing (NLP) system employing a random forest model that predicts the likelihood of pneumonia based on chest X-ray radiology reports and files its results to Epic flowsheet rows, which can then trigger clinical decision support (CDS). 17,18 To address these constraints, we began our architectural design using the five "rights" of CDS (►Table 1). 19 Given the PIS's ability to trigger native EHR workflows, we chose to use an interruptive alert (Epic BestPractice Advisory or BPA) to initiate the CDS workflow.…”
Section: Clinical Decision Support Considerationsmentioning
confidence: 99%
“…2,4 In a survey of 45 institutions, Dziorny et al 5 found that pediatric intensive care practitioners viewed CDS tools as intrusive with concerns for diminished critical thinking. Williams et al 3 acknowledge these barriers as a potential explanation for the modest impact on improving their outcome of interest.…”
mentioning
confidence: 99%
“…In this issue of the Journal of Hospital Medicine , Williams et al 3 report their findings from a pragmatic clinical trial comparing CDS to usual care at two different pediatric emergency departments (EDs) using two different electronic health record (EHR) systems. The goal of the CDS was to increase guideline‐concordant antibiotic prescribing for community‐acquired pneumonia.…”
mentioning
confidence: 99%
See 1 more Smart Citation